Achieving variable infrared emissivity modulation regions of poly(aniline) films:the effect of film surface morphology on the optical tunability. (March 2021) - Zhang, Leipeng; Xu, Gaoping; Wang, Lebin; Wang, Bo; Ren, Zichen; Dou, Shuliang; Song, Shanshan; Pan, Mengyao; Li, Xiaobai; Li, Yao
Abstract: Infrared (IR) electrochromic materials, which can dynamically regulate the IR optical properties, are particularly desirable in intelligent thermal management technology. However, for these materials, an outstanding challenge is in achieving a series of different emissivity modulation capabilities for different applications. Here, we obtain the functional poly(aniline) (PANI) films with significantly different emissivity modulation capability by tailoring the surface morphology of the PANI film. The PANI film with a non-directionally distributed nanowire-like structure (PANI2) and a rather smooth surface decorated by shallow voids (PANI6) can realize the emissivity variations from 0.321 to 0.712 and 0.190 to 0.573 in the wavelength range of 2.5–25 μm, respectively. Combined with XPS, UV–vis–NIR characterizations, and IR light propagation analysis in two representative morphologies, the reason for the thermal radiation energies of PANI2 at two states were significantly higher than those of PANI6 was proposed. As the residual PANI in PANI2 was not involved in redox reaction and remained in the emeraldine salt (ES) state, and the multiple reflections by non-directionally distributed nanowire on the surface suppressed the reflection of incident IR light. Moreover, we investigated the heat dissipation modulation capabilities of PANI2 and PANI6. PANI2 can achieve greater heat dissipation at a high emissivity state ( ε = 0.712), while PANI6 can effectively suppress heat dissipation at a low emissivity state ( ε = 0.190). Moreover, we utilized the IR thermal imager and transient thermal field analysis to evaluate the heat dissipation modulation capabilities of PANI2 and PANI6. Highlights: Poly(aniline) films with adjustable surface morphologies were successfully prepared. Poly(aniline) films with different surface morphologies exhibited different thermal radiation modulation capabilities. PANI film with non-directionally distributed nanowire-like structure can realize IR emissivity variation from 0.321 to 0.712. PANI film with a rather smooth surface decorated by shallow voids can realize IR emissivity variation from 0.190 to 0.573. The relationship between surface morphologies and IR emissivity modulation of the PANI films was investigated.